Perlindungan Hukum Terhadap Profesi Guru - Abdillah Tarigan; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
Legal protection for educational institutions is like teachers interpreted as efforts made by the government to protect teachers and other education personnel in carrying out their professional duties, both protection in legal, welfare, professional, and social aspects. Through research conducted in a normative juridical manner, this study concluded that legal protection for teachers in the educational process related to violent crimes has been fully regulated in various laws such as Law Number 14 of 2005 concerning Teachers and Lecturers and Government Regulation Number 74 of 2008 concerning Teachers. Where explained in both laws, punishment or sanction of students for the purpose of teaching by teachers is not a violent crime. Legal protection of teachers in the educational process related to acts of violence in the field of education should be applied using penal policies and non-penalty policies. The use of the policy by looking at the factors and background of criminal acts in the field of education occurs, especially by considering the purpose of the teaching process carried out by teachers.